Proteasome inhibition and cytostatic effects on human cancer cells by pyrazolone-enamines: a combined crystallographic, structural and computational study1. (2nd March 2015) - Yan, Xingchen; Xu, Jiakun; Wu, Xiaojing; Zhang, Zhongyu; Zhang, Xia; Fan, Yuhua; Bi, Caifeng
<x xml:space="preserve">Abstract</x> Interactions are possibly through hydrogen bonding of the pyrazolone ring and the hydroxyl, or the intercalation of conjugated plane.